EFFECT OF CALCIUM HYDROXIDE-BASED DRESSING ON APICAL SEALING IN IMMATURE TEETH FILLED WITH MTA - Bodanezi, Augusto; Munhoz, Etiene de Andrade; Villacis, Juanita Fierro; Bernardineli, Norberti; Bramante, Clovis Monteiro; Moraes, Ivaldo Gomes de; Garcia, Roberto Brandão (Archives of Oral Research, 2010)
OBJECTIVES: To evaluate the effects of a calcium hydroxide-based intracanal dressing on the initialapical adaptation and leakage of fillings performed with mineral trioxide aggregate (MTA) in teeth withopen apices. STUDY DESIGN: A total of 24 canals were manually prepared and randomly divided intotwo groups (n = 12). In the experimental group, root canals were dressed with calcium hydroxide-basedpaste for 21 days; in the control group, no medication was applied prior to the filling of root canalswith mineral trioxide aggregate. Apical sealing was evaluated on the basis of rhodamine B penetrationand the detection of microscopic apical defects at the filling interface (SEM). The data obtained werecompared by means of t- and Fisher’s Exact tests (á = 0.05). RESULT S: The difference in mean dyeleakage between the experimental (5.03±1.97 mm) and control (4.14±1.13 mm) groups was not statisticallysignificant (ñ < 0.05). The number of microscopic fissures at the experimental group interface (2/12)was significantly lower than that observed for the control group (9/12) (ñ < 0.05). CONCLUSIONS:The use of a calcium hydroxide-based intracanal dressing did not interfere with the initial apical sealingof immature teeth filled with MTA.